H∞ control of discrete-time Markovian jump systems with partly unknown transition probabilities - Zhang, Q.; Wang, G.; Liu, Wanquan; Zhang, Y. (Guizhou University and Chongqing University, 2010)
This paper discusses H∞ control problem for a class of discrete-time Markovian jump systems with partly unknown transition probabilities. When some elements in transition matrix are inaccessible, another approach is proposed to estimate the unknown elements. The condition for the existenceof H∞ controller is expressed by linear matrix inequalities. Finally, illustrative examples are presented to show the validity of the proposed approaches.